The effect of trial familiarisation on the validity and reproducibility of a field-based self-paced VO2max test - Lim, W; Lambrick, D; Mauger, AR; Woolley, B; Faulkner, J (Biology of Sport, 2016)
The self-paced maximal oxygen uptake (VO 2 max) test (SPV), which is based on the Borg 6-20 Ratings of Perceived Exertion (RPE) scale, allows participants to self-regulate their exercise intensity during a closed-loop incremental maximal exercise test. As previous research has assessed the utility of the SPV test within laboratory conditions, the purpose to this study was to assess the effect of trial familiarisation on the validity and reproducibility of a field-based, SPV test. In a cross-sectional study, fifteen men completed one laboratory-based graded exercise test (GXT) and three field-based SPV tests. The GXT was continuous and incremental until the attainment of VO 2 max. The SPV, which was completed on an outdoor 400m athletic track, consisted of five x 2 min perceptually-regulated (RPE11, 13, 15, 17 and 20) stages of incremental exercise. There were no differences in the VO 2 max reported between the GXT (63.5±10.1 ml∙kg-1∙min-1) and each SPV test (65.5±8.7, 65.4±7.0 and 66.7±7.7 ml∙kg-1∙min-1 for SPV1, SPV2 and SPV3, respectively; P>.05). Similar findings were observed when comparing VO 2 max between SPV tests (P>.05). High intraclass correlation coefficients were reported between the GXT and the SPV, and between each SPV test (≥.80). Although participants ran faster and further during SPV3, a similar pacing strategy was implemented during all tests. This study demonstrated that a field-based SPV is a valid and reliable VO 2 max test. As trial familiarisation did not moderate VO 2 max values from the SPV, the application of a single SPV test is an appropriate stand-alone protocol for gauging VO 2 max.